Lung cancer associated autoantibody responses are detectable years before clinical presentation. - Jared Allen; Graham Healey; Isabel Macdonald (PLoS ONE)
The EarlyCDT-Lung® test detects elevated levels of tumour-associated autoantibodies generated in response to immune recognition of cancerous cells, and these autoantibodies have previously been shown to precede clinical presentation of lung cancer. Using a longitudinal cohort from the United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) study, we have established that elevated autoantibodies can be detected an average of four years in advance of clinical presentation, and in some cases up to 8 years prior to clinical presentation. This is the first study to establish pre-diagnostic elevation of autoantibodies using samples from a longitudinal prospective clinical trial using a clinically validated and commercially available biomarker panel.